Relatório de estágio técnico profissional em medicina veterinária: higiene e inspeção de produtos de origem animal - Perera, Ana Lúcia (2023)
The Professional Technical Internship (ETP) is a great time to put into practice the theoretical knowledge acquired during the graduation period and train yourself in the area you want to work in professionally. The ETP was carried out in the area of ​​quality control, under the academic guidance of Profª. Dr. Luciana Ruschel dos Santos. Being carried out in a chicken agribusiness, from July 11th to October 27th, 2023, totaling 528 hours. At ETP it was possible to experience the routine of a slaughterhouse, accompanying quality analysts in monitoring, checking and routine procedures and filling out forms, assisting in the collection of biological materials and carrying out studies requested at critical points of control and stunning of birds. This report describes the internship location, the general and specific activities carried out during the internship period. Finally, the report presents a research project entitled “Return of consciousness, after stunning, in chickens slaughtered in accordance with the Halal religious precept”. The professional technical internship was fundamental for understanding the routine of an agribusiness and, mainly, for personal and professional maturity in the chosen area. Having knowledge of the procedures and demands within the industry is of great value for the future in the profession, and the knowledge acquired is enriching.